Summer Learning and the Effect of Schooling: Evidence from Sweden - Mikael Lindahl (Institute for the Study of Labor (IZA), 2001)
Using that schools are in session during the school year and out of session during the summer, it is possible to isolate the effect of schooling on learning. This natural experiment situation can also be used to see whether schooling compensates for disadvantageous social backgrounds. Using a new sample of Swedish sixth grade pupils, results are that math skills are lost when pupils are not in school, pupils with non-Swedish parents learn relatively more during the school year, and learning is unrelated to pupils? parents? socioeconomic level during both the summer and the school year.
Keywords: H52; I21; I28; 330; Summer learning; school-year learning; schooling effects; family background; school-year length; Bildungsniveau; Bildungsverhalten; Freizeit; Familiensoziologie; Schätzung; Schweden